A comparative study of ultimate bearing capacity of shallow rectangular footing subjected to eccentrically inclined loads. (21st September 2022) - Gupta, Sujata; Mital, Anupam
This study is presented for model tests conducted to calculate the ultimate bearing capacity (UBC) of eccentrically inclined loaded rectangular foundation on sand. Various parameters were investigated in this study included depth of embedment ( Df / B ), eccentricity ( e / B ) and the angle of inclination of applied loads ( α ). In the present study, the reduction factor is calculated as the ratio of UBC of rectangular footing subjected to eccentric and inclined load at any embedment depth to the UBC of the same footing under similar conditions but subjected to axial centric load. The reduction factor was compared with those based on the previous bearing capacity studies in this area. This comparison appears to be reasonably well. Furthermore, numerical analysis on the prototype footing was directed using commercial finite element method-based software PLAXIS 3D to authenticate the test results. A very close agreement was found between experimental and numerical analysis.